OVERCOMING HISTORIC INERTIA AS A BASIS FOR TRANSFORMING SOCIAL AND ECONOMIC SYSTEM IN RUSSIA - Yuriy K. Kondratchik (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
In Russian history we can distinguish several key stages of social and economic system transformation, when public and economic life in the country changed radically. Not many countries have got such a historic experience of reforms and living in different external and internal conditions. The article using findings of the research shows the role of historic inertia in key periods of social and economic system transformation in the Russian Federation. The author provides examples and parallels between reforms of the soviet period and present day Russian transformation processes: their common features and laws were identified. Steps aimed at overcoming historic predetermination of reforms' realization were put forward.